2015
DOI: 10.1523/jneurosci.4899-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Movement-Related Discharge in the Macaque Globus Pallidus during High-Frequency Stimulation of the Subthalamic Nucleus

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN-DBS) has largely replaced ablative therapies for Parkinson's disease.Because of the similar efficacies of the two treatments, it has been proposed that DBS acts by creating an "informational lesion," whereby pathologic neuronal firing patterns are replaced by low-entropy, stimulus-entrained firing patterns. The informational lesion hypothesis, in its current form, states that DBS blocks the transmission of all information from the basal ganglia, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…During locomotion, we found that Ca 2+ transients reliably occurred approximately 100 ms before the onset of movement and then persisted throughout the whole process of each movement. This activity was similar to a previously defined activity in the monkey motor cortex, referred to as perimovement activity (Churchland et al, 2006, 2010; Kemere et al, 2008; Zimnik et al, 2015). Perimovement activity is defined as neuronal activity occurring approximately 100 ms before, during and just after the movement and was initially found using electrophysiological recordings.…”
Section: Discussionsupporting
confidence: 87%
“…During locomotion, we found that Ca 2+ transients reliably occurred approximately 100 ms before the onset of movement and then persisted throughout the whole process of each movement. This activity was similar to a previously defined activity in the monkey motor cortex, referred to as perimovement activity (Churchland et al, 2006, 2010; Kemere et al, 2008; Zimnik et al, 2015). Perimovement activity is defined as neuronal activity occurring approximately 100 ms before, during and just after the movement and was initially found using electrophysiological recordings.…”
Section: Discussionsupporting
confidence: 87%
“…However, recent work in the NHP demonstrated that pallidal information about motor activity may be reduced by symptom-alleviating DBS [30], and that the eliminated information may relate exclusively to parkinsonian symptoms and not to intentioned motor commands [33]. Excess pallidal information reflecting a loss of motor selectivity may convey the very instructions that dictate motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in awake behaving primates, however, have provided some evidence that physiologic sensorimotor-related discharge in the basal ganglia output nucleus (GPi) may be at least partially maintained during STN or pallidal DBS [266,287]. These studies have suggested that DBS may act as a Bselective filter^that permits some sensorimotor-related modulation of the activity of neurons in the stimulated area, while eliminating transmission of pathological low-frequency neuronal activity patterns.…”
Section: Dbs Mechanism Of Actionmentioning
confidence: 99%